The Impact of Advanced Footwear Technology on the Performance and Running Biomechanics of Mountain Runners - Pedro Corbí-Santamaría; Marina Gil-Calvo; Alba Herrero-Molleda; Juan García-López; Daniel Boullosa; José Vicente García-Tormo (Applied Sciences, 2025)
In recent years, advanced footwear technology (AFT) has been shown to improve performance in long-distance road running by altering biomechanics and perceived comfort. This type of footwear is now being marketed for mountain running, although its effects in such races remain unevaluated. This study aimed to examine the impact of AFT on performance, biomechanics, and perceived comfort during a simulated mountain running event. Twelve trained mountain runners participated in a 3-day experiment, with a 7-day recovery between sessions. On the first day, a maximal aerobic speed test assessed the runners’ performance levels. On the second day, participants familiarized themselves with a 5.19 km mountain circuit and comfort scale. On the third day, they completed two time trials on the same circuit, separated by 30 min of passive recovery, using conventional and AFT shoes in a randomized order. Physiological and biomechanical variables were recorded, including body mass, blood lactate, running biomechanics, vertical stiffness, shoe comfort, and rating of perceived exertion (RPE). The findings indicate that AFT does not improve performance or physiological responses during a simulated mountain race, regardless of segment (uphill, downhill, or mixed). However, AFT significantly alters running biomechanics, reducing step frequency and increasing the vertical oscillation of the center of gravity, especially in uphill and downhill sections. While overall comfort remained unchanged, specific differences were observed with AFT. Coaches and practitioners should consider these findings when using AFT in mountain running training or competition.